Conservation planning for priority crop wild relatives in the SADC region - Bioversity International; University of Birmingham (2016)
The brief summarizes the results of the crop wild relative checklist development, its prioritization, projected impact of climate change on the distribution of priority CWR, and the identification of in situ conservation sites in the Southern African Development Community (SADC) region, carried out within the project “In Situ Conservation and Use of Crop Wild Relatives in three ACP countries of the Southern African Development Community (SADC) region" (2014 – 2016).